2012
DOI: 10.17221/156/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea types and irrigation on crop uptake, soil residual, and loss of nitrogen in maize field on the North China Plain

Abstract: Water and nitrogen managements are both very important to increase crop yield. An experiment was carried out in split plot design to study the effects of urea types (normal urea and coated urea) and irrigation on soil and fertilizer nitrogen use in maize (Zea mays L.) field in 2006 and 2007. Irrigation was used as main plot, and urea types were used as split-plot. Two irrigation levels, no irrigation in the whole growth duration and 85 mm irrigation at the blister stage, were designed. There were five nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This could be attributed to higher nitrogen losses from uncoated urea and reduced nitrogen losses from coated urea fertilizers. When compared to regular urea, Ning et al [44] found that controlled release urea can boost total nitrogen uptake by aboveground organs and soil residual while lowering loss. Coated urea fertilizers may reduce nutrient losses by enhancing nutrient utilization efficiency.…”
Section: Nitrogen Uptakementioning
confidence: 99%
“…This could be attributed to higher nitrogen losses from uncoated urea and reduced nitrogen losses from coated urea fertilizers. When compared to regular urea, Ning et al [44] found that controlled release urea can boost total nitrogen uptake by aboveground organs and soil residual while lowering loss. Coated urea fertilizers may reduce nutrient losses by enhancing nutrient utilization efficiency.…”
Section: Nitrogen Uptakementioning
confidence: 99%
“…To avoid N losses in soil, there is a need to use some slow release fertilizers, such as sulfur-coated urea, that can make essential nitrogen nutrient available and an alternative way of application, as salt accumulation in root zone can cause root burn. Coated urea has been reported to be more effective in reducing environmental pollution and increasing crop yield (Ogola et al 2002;Shao et al 2008;Ning et al 2012). Sulfur-containing compounds/metabolites can be used as fertilizers to reverse the effects of abiotic stresses in agricultural crops (Khan et al 2014a, b, c).…”
Section: Introductionmentioning
confidence: 99%